Shuttle-Based Storage and Retrieval System 3d Model Improvement and Development - Nevliudov, I.; Yevsieiev, V.; Maksymova, S.; Klymenko, O.; Vzhesniewski, M. (My University, 2023)
The development of new design solutions for Radioshuttle will increase the storage density of heterogeneous goods, increase the efficiency and productivity of warehouse logistics, reduce the cost of renting warehouse space and reduce the negative impact on the environment, which makes this development extremely relevant and necessary in modern logistics. Authors proposed to improve the designs of the Radioshuttle, through the use of the Mecanum Wheel. To test this, the authors designed a 3D model of a Radioshuttle with a Mecanum Wheel using Autodesk Fusion 360 while maintaining overall dimensions and a 3D model of rack structure.
I
Keywords: Shattle; Storage; Retrieval System; Warehouse Management System; Warehouse 4.0.